The Synergies Between Understanding Belief Formation and Artificial Intelligence - Lumbreras, Sara (Frontiers in Psychology, 2022)
Understanding artificial intelligence and belief formation have interesting bidirectional synergies. From explaining the logical derivation of beliefs and their internal consistency, to giving a quantitative account of mightiness, artificial intelligence still has plenty of unexploited metaphors that can illuminate belief formation. In addition, acknowledging that artificial intelligence should integrate itself with our belief processes (mainly, the capacity to reflect, rationalize and communicate that is allowed by semantic coding) makes it possible to focus on more promising lines such as Interpretable Machine Learning.